(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
A "mid-Carnian" transgressive succession, developed between the Breno carbonate platform and the semiarid coastal carbonates-sabkhas facies of the S. Giovanni Bianco Fm., is recorded in the northern Bergamasc Alps. This episode is characterized by the presence of two stratigraphic markers: a) Dark grey shales and siltstones ("Black Pelites"), considered previously as the northern closure of the Gorno-Lower S. Giovanni Bianco Fms., but re-interpreted as the western pinch-out of the Lozio Shale depositional system. The Early Carnian Lozio Shale was deposited first in the Valle di Scalve-Lozio trough and later covered the carbonate platform (Breno Fm.). b) Fossiliferous, open subtidal limestones, marls and burrowed marly limestones ("Bioclastic Horizon") of the northern Bergamasc Alps. The spreading of shales and siltstones represents the first transgressive stage of the last Carnian sequence in Lombardy, after the "mid- Carnian" (Julian substage) regional carbonate platform crisis (top of the Valcamonica Breno Fm.). The "Bioclastic Horizon" records the mfs represented by normal, open marine facies, identified and correlated throughout the Bergamasc Alps. Different petrographic and chemical characters between the Lozio Shale - "Black Pelites" and the Gorno-San Giovanni Bianco Fms. suggest different source areas: the former units are characterized by clasts derived from a metamorphic-intrusive area (placed northward and westward), whereas the latter units are characterized by prevailing volcaniclastic material. A climatic change (from arid to relatively humid conditions) may be invoked to explain the crisis of the "mid-Carnian" carbonate platforms in the western Southern Alps and the regional spreading of fine-grained terrigenous material.